2019
DOI: 10.1063/1.5125141
|View full text |Cite
|
Sign up to set email alerts
|

An updated applied formulation for the Goubau transmission line

Abstract: The Goubau line is a unique transmission line that consists of only a single conductor. Its unique properties make it a solid candidate for low-loss RF propagation and wireless power transfer applications. However, the applied theory of this line that has been established thus far is missing key details of the line's characteristics. Namely, no discussion has been made on the Goubau line's ohmic current distribution or its effective characteristic impedance that would be used in RF/microwave circuit analysis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…For the surface wave, Vaughn showed that the displacement current acts as the return path for the conduction current such that the total current is zero as required by Maxwell's equations. 17 Using the continuity of the tangential magnetic field at r ¼ a, the current can also be expressed as…”
Section: B Definition Of Voltage and Currentmentioning
confidence: 99%
See 1 more Smart Citation
“…For the surface wave, Vaughn showed that the displacement current acts as the return path for the conduction current such that the total current is zero as required by Maxwell's equations. 17 Using the continuity of the tangential magnetic field at r ¼ a, the current can also be expressed as…”
Section: B Definition Of Voltage and Currentmentioning
confidence: 99%
“…16 Finally, Vaughn and Peroulis obtained capacitance and inductance values by considering a coaxial cable that has an outer radius such that the same power is transported in the coaxial mode as in the surface wave mode. 17 In contrast to these approaches, we will calculate the inductance, capacitance, conductance, and resistance directly from the surface wave field expressions. Moreover, this approach is then generalized to multiple wires by assuming that the field is approximated by surface waves supported on the individual wires.…”
Section: Introductionmentioning
confidence: 99%
“…The need for low-loss and ultra-wideband wave-guiding systems in the GHz and THz regions triggered renewed interest in different types of the Goubau line. The associated problems were extensively revisited within the last decade [ [5] , [6] , [7] , [8] , [9] ] parallel to the rapid development of high-speed broadband communication technologies such as 5G and 6G networks [ 10 ]. Note, that in the current data transfer applications, the distances for wave-guiding have been reduced drastically to the dimensions of a single board or integrated.…”
Section: Introductionmentioning
confidence: 99%
“…T He planar Goubau line (PGL) is a single-conductor planar waveguide that can propagate a surface wave with a quasi-TM mode (hybrid EH mode). The displacement currents surrounding its metal strip act as return currents [1], reducing ohmic losses compared to conventional multi-conductor planar waveguides. Moreover, radiation losses can also be minimized by the use of electrically-thin substrates, becoming a low-loss planar waveguide for terahertz frequencies, with a demonstrated attenuation coefficient of 0.32 Np∕mm at 1 THz [2].…”
Section: Introductionmentioning
confidence: 99%